Computer and information security handbook - edited by John R. Vacca (Morgan Kaufmann Publishers, an imprint of Elsevier, 2017)
Computer and Information Security Handbook, Third Edition, provides the most current and complete reference on computer security available in one volume. The book offers deep coverage of an extremely wide range of issues in computer and cybersecurity theory, applications, and best practices, offering the latest insights into established and emerging technologies and advancements